Environmental DNA as a non-invasive alternative for surveying aquatic communities in tank bromeliads - Lopes, Carla Martins [UNESP]; Santos, Marcus Thadeu T. [UNESP]; Baêta, Délio [UNESP]; Sabbag, Ariadne Fares [UNESP]; Haddad, Célio Fernando Baptista [UNESP] (CSIRO Publishing, 2021)
Tank bromeliads provide a freshwater microhabitat for a rich aquatic community, including amphibian species. Some of these amphibians are threatened, among other factors, because their host plants are also threatened. DNA traces left behind by amphibians in the water accumulated in bromeliads provide us a clue to track the presence and geographical distribution of these species in the environment, even when they have a low population abundance. We used an environmental DNA metabarcoding approach to survey three bromeligenous or bromelicolous amphibian species distributed in the Brazilian Atlantic forest. The three species have a low population abundance or are not detected in the field by using traditional methods for up to 100 years. No DNA trace of our target species was identified among the eDNA samples analysed. However, we successfully identified the DNA of one tribe, two genera and nine amphibian species in the bromeliads surveyed. Our results support the high sensitivity and the non-invasive characteristic of eDNA metabarcoding for surveying bromeligenous or bromelicolous amphibians. We also highlight that more amphibian species could eventually use bromeliads as shelter than has been previously thought, evidencing the importance for further investigations about interactions and conservation status of amphibians and bromeliads.
Keywords: amphibian survey; eDNA; metabarcoding; non-invasive survey; threatened species